Synthetic Polyploidy in Grafted Crops - Ruiz, Marta; Oustric, Julie; Santini, Jérémie; Morillon, Raphaël (Frontiers in Plant Science, 2020)
Synthetic polyploids have been extensively studied for breeding in the last decade. However, the use of such genotypes at the agronomical level is still limited. Polyploidization is known to modify certain plant phenotypes while leaving most of the fundamental characteristics apparently untouched. For this reason, polyploid breeding can be very useful for improving specific traits of crop varieties such as quality, yield, or environmental adaptation. Nevertheless, the mechanisms that underlie polyploidy-induced novelty remain poorly understood. Ploidy-induced phenotypes might also include some undesired effects that need to be considered. In the case of grafted or composite crops, benefits can be provided both by the rootstock´s adaptation to the soil conditions and by the scion´s excellent yield and quality. Thus, grafted crops provide an extraordinary opportunity to exploit artificial polyploidy, as the effects can be independently applied and explored at the root and/or scion level, increasing the chances of finding successful combinations. The use of synthetic tetraploid rootstocks may enhance adaptation to biotic and abiotic stresses in perennial crops such as apple or citrus. However, their use in commercial production is still very limited. Here, we will review the current and prospective use of artificial polyploidy for rootstock and scion improvement and the implications of their combination. The aim is to provide insight into the methods used to generate and select artificial polyploids and their limitations, the effects of polyploidy on crop phenotype (anatomy, function, quality, yield and adaptation to stresses) and their potential agronomic relevance as scions or rootstocks in the context of climate change.